Antenatal Care Service Utilization Among Adolescent Pregnant Women–Evidence From Swabhimaan Programme in India - Fulpagare, Prakash H.; Saraswat, Abhishek; Dinachandra, Konsam; Surani, Nikita; Parhi, Rabi N.; Bhattacharjee, Sourav; S, Somya; Purty, Apollo; Mohapatra, Babita; Kejrewal, Nita; Agrawal, Neeraj; Bhatia, Vikas; et al. (Frontiers in Public Health, 2019)
Purpose: Pregnant adolescent girls (15-19 years) are more vulnerable to poor health and nutrition than adult pregnant women because of marginalization and lack of knowledge about the antenatal care (ANC) services. Present study aims to test this hypothesis and also assess determinants of ANC services utilization among currently adolescent pregnant women. Methods: Data was drawn from baseline survey of the SWABHIMAAN project which had been conducted in three states of India: Bihar, Chhattisgarh, and Odisha. Out of a total 2573 pregnant women (15-49 years) included in the sample, about 10% (N=278) were adolescent girls (15-19 years) at the time of survey and rest were adults. Sample was selected from population using simple random sampling and information was collected using pre-tested questionnaires. Results: For all indicators of ANC service utilization, performance of adolescent pregnant women was better than adult pregnant women. However, significant variations were reported in level of services received by adult pregnant women for different indicators. Religion, wealth, food insecurity, Village Health Sanitation and Nutrition Day meeting, Public Distribution System and Integrated Child Development Services entitlements and knowledge of family planning methods had a significant effect on the ANC service utilization. Conclusion: Adolescent pregnant women have shown the better utilization of selected indicators than their adult counterparts. Utilization of full ANC services starting from first trimester itself for adolescent pregnant women is an urgent need in present context. Intervention program must pay attention to such adolescent married girls who are entering into motherhood phase of their lives.